Struktur Komunitas Mangrove di Pesisir Pantai Cemara Selatan Kabupaten Lombok Barat sebagai Bahan Penyusunan Modul Ekologi - Safnowandi Safnowandi (Universitas Sulawesi Barat, 2021)
This type of research is comparative descriptive and development research. The results showed that there were 4 species of mangroves found in sandy and muddy substrates, namely: 1) Rhizophora apiculata; 2) Rhizophora mucronata; 3) Avicennia alba; and 4) Sonneratia alba. The abundance of mangrove plants on sandy substrate is Sonneratia alba as many as 215 species. Meanwhile, the muddy substrate was Rhizhophora mucronata with 182 species. Mangrove diversity is low, with the diversity index value in the sandy substrate of 0.023 - 0.612 and in the muddy substrate 0.138 - 0.433. The closeness of mangroves is also classified as low with a range of closeness index values ​​in the sandy substrate from 0.005 to 0.153 and in the muddy substrate from 0.034 to 0.108. For species dominance, it is only found in sandy substrates, namely Sonneratia alba species which are classified into moderate dominance. As for the validation results of teaching materials in the form of an ecology module, based on the results of the validation of teaching materials experts and validation of content and material experts, the results were 87.55% with very good qualifications. With the results of the validation, the teaching material in the form of an ecology module is suitable for use without revision.